A Study on Self-Regulatory Capacity in Learning English Grammar of High Schoolers in Gia Lai - Lê Nguyễn Thanh Uyên (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The study is aimed at investigating the self-regulatory capacity (SRC) of tenthgraders in Gia Lai province in learning English grammar, thereby suggesting some ways to improve the quality of teaching and learning English grammar at high school